Editorial: Genotype-Phenotype Correlation in Parkinsonian Conditions - Marsili, Luca (2021)
With the diffusion of cost-effective genetic analyses, an increase in the spectrum of reported genetic variants associated with sporadic Parkinson’s disease (sPD) (e.g., glucocerebrosidase— GBA) and monogenic parkinsonisms (dominant, recessive, and atypical forms) has been achieved. Each single variant may be associated to distinct prominent phenotypic characteristics helpful for diagnostic and prognostic purposes, thus ushering the era of precision medicine for movement disorders.